Telemedicine to Support Heart Failure Patients during Social Distancing: A Systematic Review - Serlie Fatrin; Salwa Auliani; Samuel Pratama; Thiara Maharani Brunner; Bambang Budi Siswanto (Ubiquity Press, 2022)
Background: Heart failure (HF) has been described as an emerging pandemic as its prevalence continues to rise with a growing and aging population. HF patients are more vulnerable to infections with higher risk of hospitalisation, morbidity, and mortality. During this COVID-19 pandemic, telemedicine has emerged as an alternative to usual out-patient care. This study aimed to systematically review available literature regarding the effect of telemedicine on mortality, health-related quality of life (HR-QoL), and hospitalisation rate of HF patients. Method: A literature search was conducted on five databases (PubMed, Medline, EMBASE, SCOPUS and Cochrane Central Database) up to 21st May 2022. Data from studies that fulfilled the eligibility criteria were collected and extracted. Included studies were critically appraised using suitable tools and extracted data were synthesized qualitatively. Results: A total of 27 studies were included in the qualitative synthesis with a total of 21,006 patients and sufficient level of bias. Reduction in the mortality rate, HF-related hospitalisation rate, and improvement in the HR-QoL were shown in most of the studies, although only some were statistically significant. Conclusions: The use of telemedicine is a promising and beneficial method for HF patients to acquire adequate health care services. Further studies in this field are needed, especially in developing countries and with standardized method, to provide better services and protections for HF patients. Telemonitoring and patient-centred partnership via interactive communication between healthcare team and patients is central to successful telemedicine implementation. PROSPERO Registration Number: CRD42021271540.